STUDI MAKROBENTOS DI PESISIR PANTAI KARANG-KARANGAN KECAMATAN BUA KABUPATEN LUWU - Akhmad Syakur (Universitas Cokroaminoto Palopo, 2021)
This study aims to see the abundance of macrobenthos and those that dominate macrobenthos on the coast of Karang-Karangan village, Bua sub-district, Luwu district and also to see its diversity index. This research was conducted in September 2020 on the coast of Karang-Karangan, Bua District, Luwu Regency. The type of research used in this research is descriptive research that describes the existence of macrobenthos on the coast of Karang-Karangan. The data analysis technique used in this research is descriptive data. The results of the research on the diversity of macrobenthos showed a low level of diversity, namely station I 0.57, station II 0.22 and station III 0.43.